การประเมินความสามารถทนเค็มของต้นกล้าข้าวพันธุ์พื้นเมืองไทยและการเชื่อมโยงทั้งจีโนมกับลักษณะทนเค็ม - นพคุณ คุณผลวัฒนา (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This study aims to evaluate the salt tolerant (9 dS/m) ability of 174 local Thai rice cultivars and use the data for genome-wide association analysis to identify the loci involving in salt stress response. Shoot and root fresh weight, shoot and root dry weight, leaf relative water content, cell membrane stability and yield components were determined when 14-day-old rice seedlings were treated with NaCl solution, causing the soil salinity at 9 dS/m during the experimental period.  Moreover, stability index was used to identify the ability of salt tolerance. Based on principal component and cluster analysis using physiological parameters and stability index, the clusters of rice accessions were generated according to salt tolerant ability. The rice accessions that may contain the important salt tolerant genes were Luang Pratahn, Jao Khao, RD1, Lao Taek, Ai Tai, E-Puang, Sai Yud, Dam Dahng, Pawng Aew, Khao Gaw Diaw, Leuang Tia, Khitom Pan and Niaw San-pah-tawng. Each physiological response dataset was used for genome-wide association with 223,800 SNPs database to reveal the significant SNPs that associated with physiological response parameters (logarithm of significant level [-log10(P)] less than 10-6). There were 30 SNPs, locating on exons of 30 loci associating with salt tolerant ability.  They are distributed on all chromosomes, except chromosome 5.  Salt injury score trait was associated with 4 SNPs on chromosome 1, 3, 7 and 11.  Shoot fresh weight under salt stress (S_SFW) was associated with 7 SNPs on chromosome 1, 3, 4, 6, 7 and 10, while shoot dry weight under salt stress (S_SDW) was associated with 2 SNPs on chromosome 10 and 11. Root fresh weight under salt stress (S_RFW) associated with 5 SNPs on chromosome 1, 7, 8 and 12, four of which were identified by other parameters, which were shoot fresh weight (S_SFW) and root dry weight under salt stress(S_RDW). Root dry weight under salt stress (S_RDW) was associated with 7 SNPs on chromosome 2, 7, 8, 10, 11 and 12. Stability indices of SFW, RFW, SDW and RDW were associated with 2, 4, 1 and 1 SNPs, respectively. When the phenotypes were associated with SNPs on promoters, 9 the putative salt stress associated genes were found on chromosome  3, 4, 6, 9, 10, 11 and 12. They were not consistent with SNPs predicted by association with SNPs on exons.  These loci should be validated for the roles in salt tolerance before application in rice breeding program in the future.